THE USE OF LEGAL PROTECTION ON BRANDS BASED ON THE CONSTITUTION OF THE REPUBLIC OF INDONESIA NUMBER 20 OF 2016 CONCERNING BRANDS AND GEOGRAPHICAL INDICATIONS - Sabilla Octavina, Zarah; Hendrawan, Daniel (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The efforts to protect the law on brands are a general step given by the State to brand owners aimed at preventing the occurrence of an act of brands infringement. The method used in this research is normative legal research. Based on Article 1 of the Constitution Number 20 of 2016 concerning Brands and Geographical Indications, what is meant by a brands is a sign that can be displayed graphically in the form of an image, logo, name, word, letter, number, color arrangement, in the form of 2 (two) dimensions and / or 3 (three) dimensions, sound, hologram, or a combination of (two) or more of these elements to distinguish goods and / or services produced by persons or legal entities in the activities of trading in goods and / or services. The results of this study are to find out how the application of legal protection to brands and legal certainty for brand owners, the importance of brands with legal protection, one of which is the creation of a sense of justice for brand owners and can be felt by the community.